2018
DOI: 10.2169/internalmedicine.9670-17
|View full text |Cite
|
Sign up to set email alerts
|

Early Combination Therapy with Corticosteroid and Nucleoside Analogue Induces Rapid Resolution of Inflammation in Acute Liver Failure due to Transient Hepatitis B Virus Infection

Abstract: Objective Patients with acute hepatitis B sometimes develop acute liver failure (ALF), which has a poor prognosis. The efficacy of nucleoside analogue (NA) monotherapy for ALF due to transient hepatitis B virus infection (HBV-ALF) remains controversial. Further investigations are necessary in nations with a shortage of donor livers for liver transplantation. In the present study, we aimed to clarify the efficacy of combination therapy with corticosteroid (CS) and NA in the treatment HBV-ALF. Patients We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Recently, the US‐ALF Study Group reported that clinically significant bleeding was uncommon in patients with ALF . Bleeding complications were also uncommon even in our patients with INR >3.0 and/or those treated with corticosteroid according to our limited experience, and we could have reduced the usage of fresh frozen plasma to much lower levels than that in 1990s. Furthermore, intracranial pressure monitor placement, which is one of the major bleeding sites in the above mentioned article, became unnecessary because of the high recovery rate of consciousness.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Recently, the US‐ALF Study Group reported that clinically significant bleeding was uncommon in patients with ALF . Bleeding complications were also uncommon even in our patients with INR >3.0 and/or those treated with corticosteroid according to our limited experience, and we could have reduced the usage of fresh frozen plasma to much lower levels than that in 1990s. Furthermore, intracranial pressure monitor placement, which is one of the major bleeding sites in the above mentioned article, became unnecessary because of the high recovery rate of consciousness.…”
Section: Discussionmentioning
confidence: 73%
“…Although various extracorporeal devices have been proposed as ALS, there is no consensus about the best method. We have analyzed patients with ALF of various etiologies and reported the clinical, biochemical, radiological, and pathological features, treatment response and outcome . From our experience, despite the lack of survival benefit of ALS, evidence for the benefit of restoration of consciousness is important in that it enables a patient to show the will for treatment, start enteral nutrition, and remove a respirator and respirator‐associated infections.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the role of HBeAb in de novo HBV infection needs to be re‐understood in pediatric population. In addition, the use of steroids in adult liver transplantation recipients may stimulate the glucocorticoid‐responsive element in the genome of HBV which results in the upregulation of HBV gene expression; therefore, steroid use was considered to increase the risk of postoperative HBV infection in liver transplantation recipients . In this study, all the recipients followed the same regimen of steroid use, and none of the recipients with de novo HBV infection had acute rejection after transplantation, which requires steroid bolus therapy.…”
Section: Discussionmentioning
confidence: 95%
“…The early combined use of NAs and GCs could be a good option to reverse the potential deterioration in patients with HBV-related liver failure. A recent study reported that early combination therapy with corticosteroid and NAs induces rapid resolution of inflammation in ALF due to transient HBV infection (24). It has been shown that with sufficient doses of NAs, GCs cannot affect the replication of HBV (12).…”
Section: The Applied Status Of Gcs Therapy In Liver Failurementioning
confidence: 99%
“…The idea of using GCs during acute liver failure has circulated for so many years, but, so far, no meaningful work has provided conclusive evidence of its therapeutic efficacy, except in the field of autoimmune etiology. Beyond the east/west demarcation, current data availing GC's use in liver failure revealed benefits that appeared marginal and were no longer present upon adjustment (10), came from evidence recorded in non-randomized studies (22), or were other ones carried out in small groups of patients (23, 24). More results should be confirmed using a larger randomized clinical trial to in order to arrive at better definitions in terms of treatment schedules according to different clinical settings.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%